Arduino-Based Automatic Sliding Door Design: Arduino-Based Automatic Sliding Door Design - Reza Alamsyah; Allwine Allwine (Jurnal Mantik, 2020)
Conventional doors usually consist of a home key and a saddle key to open it. Generally, office doors can be made more practical. The door will automatically open if there is a stimulus (physical energy) that moves it. For example, when someone wants to enter the room the door will automatically open. Doors like this can be designed using automatic control using embedded system equipment such as a microcontroller. This automatic door system can be designed using automatic controls combined with sensors and DC motors. In terms of input equipment used PIR (Passive Infra-Red) sensors that can detect the presence of humans approaching the door. The PIR sensor will send a signal to the Arduino process unit in which there is a microcontroller chip. The microcontroller will send the processing data to the DC motor so that it can open and close the door automatically.